Da'wah Hidayatullah Communication Strategy in Socializing Islamic Religion in Tana Toraja District - Muhammad Saleh; Muhammad Farid; Muh Akbar (Research Synergy Foundation, 2021)
The communication strategy carried out by the Hidayatullah Da’wah Institute in Tana Toraja Regency is an effort to spread Islamic education in Indonesia. The urgency of this research is increasingly visible because the Hidayatullah Institute is in a Christian-majority arxea. This study aims to describe the communication strategies carried out by the Hidayatullah Da’wah Institute in disseminating Islamic education in Toraja Regency and aims to determine the supporting and inhibiting factors of the Hidayatullah Da’wah Institute in disseminating Islamic religious education in Tana Toraja Regency. The research method used is descriptive qualitative using an organizational communication research approach—data obtained through observation, in-depth interviews (in-depth interview), and documentation. The purposive sampling technique determines informants according to their position and work position in the organization. This study indicates four communication strategies by the Hidayatullah Da’wah Institute, namely (1) through the marriage system. (2) Moving door to door. (3) Through the field of recitation and (4) Through the field of politics. The results of further research are the supporting and inhibiting factors of the Hidayatullah Da’wah Institute. Supporting factors (1) Strong militancy of Hidayatullah cadres (internal). (2) full support from the government (external). The inhibiting factor (1) The lack of Hidayatullah cadres in Tana Toraja Regency (internal). (2) Lack of network facilities and strong local traditions of Tana Toraja (external). This research has a research limitation which only describes aspects of the communication strategy carried out by the Hidayatullah Da’wah Institute in Tana Toraja Regency. This research is interesting because the object of research is in areas with the majority outside of Islam.